Quality of governance and tax revenue generation in West Africa: a political process theory perspective / Fatimoh Mohammed and Soliha Sanusi - Mohammed, Fatimoh; Sanusi, Soliha (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2020)
This article examined governance quality indicators such as control of corruption, political stability, voice and accountability and GDP per capita growth on tax revenue generation. This study conducted a panel analysis on all the variables from 15 West African countries between 2009 -2018. The pull result indicated significant and positive relationship with control of corruption, political stability and tax revenue generation. Regulatory quality typified a negative and insignificant relationship; depicting the weak nature of regulatory structures towards revenue mobilization in the West African region. This study suggests digitalization of the tax system, formidable regional economic integration against illicit outflows and improvement of governance culture in order to drive tax compliance and revenue mobilization. Future research should consider the relationship between tax revenue generation and variables such as tax payers’ confidence and tax system digitalization.